A way forward: from the 2020 Africa Conference Assuring food and nutrition security in Africa by 2020 -- prioritizing actions, strengthening actors, and facilitating partnerships, Kampala, Uganda, April 1–3, 2004 - International Food Policy Research Institute (International Food Policy Research Institute, 2004)
Africa may at last be poised to make real progress on achieving food and nutrition security. Although the number of Africans who are undernourished has been on the rise for decades and now stands at about 200 million people, a new commitment to change has emerged both among African leaders and in the international community. To help determine how to bring about actions that will assure food and nutrition security, the 2020 Vision Initiative of the International Food Policy Research Institute (IFPRI) facilitated an African-owned and African-driven conference in Kampala, Uganda, on April 1–3, 2004. The conference, “Assuring Food and Nutrition Security in Africa by 2020: Prioritizing Actions, Strengthening Actors, and Facilitating Partnerships,” brought together more than 500 traditional and new actors and stakeholders representing perspectives and experiences from all major sectors across Africa. This statement on the way forward from the 2020 Africa Conference was developed by the Conference Advisory Committee (CAC), comprising about 35 distinguished African policymakers, civil society leaders, and researchers as well as representatives of cosponsor institutions. A draft of this statement was shared with CAC members and participants at the 2020 Africa Conference, and a subcommittee of the CAC then finalized it. This statement is designed not as an immutable set of instructions, but as a set of guidelines, or a framework, pointing the way toward a food- and nutrition-secure Africa.... Our hope is that this statement will contribute to the efforts by individuals and institutions to ensure healthy and productive lives for all Africans.